DNA metabarcoding provides new insight into the diet of invasive chital deer (Axis axis) in a tropical savanna landscape - Matthew J. Quin; Ben T. Hirsch; Lin Schwarzkopf; Kurt Watter; Anthony Pople; Jan M. Strugnell (Ecosphere, 2025)
Abstract The introduction of non‐native species into new environments can cause significant ecological harm and is considered a major conservation threat. As populations of invasive species continue to establish and increase across the globe, novel methods can provide new insights into their biology and potentially aid in management. In this study, we examined the diet of non‐native chital deer (Axis axis) in a tropical savanna environment in northern Australia. Using DNA metabarcoding of fecal samples, we described the dietary items consumed by 149 individuals over a two‐year sampling period and associated each item with individual body condition. The DNA metabarcoding method detected significantly more dietary items consumed by individual chital deer at each of the taxonomic levels (family, genus, and species) when compared with previous analyses. We observed marked differences in diet composition across multiple seasons and sites. Significantly more sequences from the genera Terminalia, Diospyros, Jasminum, and Hakea were detected in samples collected from individuals in poor condition during the dry season, suggesting that a different suite of food resources is being consumed by a subset of individuals during periods when forage quantity and quality is low. Most notably, our results indicated that chital are consuming a browse‐dominated diet throughout the year, differing from previous macroscopy analyses which suggested chital are predominantly grazers during the wet season in northern Australia. Our findings give support for the use of DNA metabarcoding to qualitatively assess diet composition compared to macroscopic analysis and suggest that the restricted availability of food during the dry season may result in the consumption of poor quality and detrimental dietary items.